IDENTIFIKASI KEMAMPUAN PENALARAN SISWA KELAS XI DI MAN 4 BANTUL PADA SUHU DAN KALOR - Nur Arviyanto Himawan; Jumadi Jumadi; Edy Purwanto (EDUSAINS, 2020)
AbstractReasoning skill is essential for students to have to face the challenges of the 21st century. This study aims to determine the percentage of students' reasoning skills based on deductive hypothesis, inductive hypothesis, and reflective abstraction. This research used a descriptive method involving 26 students of Islamic Senior High School 4 Bantul. The data from tests were analyzed quantitatively, while the data from interviews were analyzed qualitatively as supporting data. The results showed that the indicators of deductive hypothesis: Aspects of explaining a fact, there are 62% of students explained the facts correctly but were incomplete and 38% of students explained the facts incorrectly; Aspects of making conclusions deductively, there are 77% of students made correct conclusions but were incomplete and 23% of students made incorrect conclusions. Based on inductive hypothesis indicators: Aspects of making conclusions inductively, all students can make conclusions, but incorrect in associating equations; Aspects of giving reasons, all students gave incorrect reasons. Based on indicators of reflective abstraction: Aspects of developing concepts, there are 50% of students who can connect concepts in a case correctly and 50% of students incorrectly connect concepts in a case. This showed that students' reasoning skill is still low. AbstrakKemampuan penalaran penting dimiliki oleh siswa untuk menghadapi tantangan abad 21. Penelitian ini bertujuan untuk mengetahui persentase kemampuan penalaran siswa berdasarkan hipotesis deduktif, hipotesis induktif dan abstraksi reflektif. Penelitian ini menggunakan metode deskriptif yang melibatkan 26 siswa MAN 4 Bantul. Data dari tes dianalisis secara kuantitatif, sedangkan data dari wawancara dianalisis secara kualitatif sebagai data pendukung. Hasil penelitian menunjukkan bahwa pada indikator hipotesis deduktif: Aspek menjelaskan fakta, terdapat 62% siswa yang menjelaskan fakta secara tepat namun kurang lengkap dan 38% siswa kurang tepat dalam menjelaskan fakta; Aspek membuat kesimpulan secara deduktif, terdapat 77% siswa membuat kesimpulan dengan tepat namun kurang lengkap dan 23% siswa membuat kesimpulan yang kurang tepat. Berdasarkan indikator hipotesis induktif: Aspek membuat kesimpulan secara induktif, semua siswa dapat membuat kesimpulan, namun tidak tepat dalam mengaitkan persamaan; Aspek memberi alasan, semua siswa memberikan alasan yang kurang tepat. Berdasarkan indikator abstraksi reflektif: Aspek pengembangan konsep, sebanyak 50% siswa mampu menghubungkan konsep dalam suatu kasus secara tepat dan 50% siswa kurang tepat dalam menghubungkan konsep pada suatu kasus. Hal ini menunjukkan kemampuan penalaran siswa masih rendah.